(untitled) (International Seven Journal of Multidisciplinary, 2025)
This study analyzes the penal system in Rio Grande do Sul and its impact on the reintegration of individuals deprived of liberty, using recent official data and reports (RELIPEN 2024, SUSEPE, CNJ, RS Public Defender’s Office). The research examines indicators such as the number of prisoners, demographic profile, educational and work activity offerings, overcrowding, vacancy shortages, and state reintegration policies. The results indicate progress in training and educational participation, but highlight significant structural obstacles, such as overcrowding, low educational attainment, and racial inequalities. The conclusion is that the system’s effectiveness depends on structural and intersectoral actions, including expanded vacancies, professional certification, and post-release monitoring.